Influence of light/dark cycle and orexins on breathing control in green iguanas (Iguana iguana) - Fonseca, Elisa M. [UNESP]; Vicente, Mariane C. [UNESP]; Fournier, Stephanie; Kinkead, Richard; Bícego, Kênia C. [UNESP]; Gargaglioni, Luciane H. [UNESP] (Springer Nature, 2020)
Light/dark cycle affects the physiology of vertebrates and hypothalamic orexin neurons (ORX) are involved in this function. The breathing pattern of the green iguana changes from continuous to episodic across the light/dark phases. Since the stimulatory actions of ORX on breathing are most important during arousal, we hypothesized that ORX regulates changes of breathing pattern in iguanas. Thus, we: (1) Localized ORX neurons with immunohistochemistry; (2) Quantified cyclic changes in plasma orexin-A levels by ELISA; (3) Compared breathing pattern at rest and during hypoxia and hypercarbia; (4) Evaluated the participation of the ORX receptors in ventilation with intracerebroventricular microinjections of ORX antagonists during light and dark phases. We show that the ORX neurons of I. iguana are located in the periventricular hypothalamic nucleus. Orexin-A peaks during the light/active phase and breathing parallels these cyclic changes: ventilation is higher during the light phase than during the dark phase. However, inactivation of ORX-receptors does not affect the breathing pattern. Iguanas increase ventilation during hypoxia only during the light phase. Conversely, CO2 promotes post-hypercarbic hyperpnea during both phases. We conclude that ORXs potentiate the post-hypercarbic (but not the hypoxic)-drive to breathe and are not involved in light/dark changes in the breathing pattern.